Dampak Cognitive Moral Development Terhadap Kejujuran Pelaporan Anggaran - Tommy Wijaya (Universitas Katolik Soegijapranata Semarang, 2020)
Abstract This study aims to analyze the impact of Cognitive Moral Development in honesty budget reporting because honesty in employees is important in the success of a company so it needs to be formed early. The development of Cognitive Morals is justification in making decisions relating to social actions to act ethically. Honesty of budget reporting in this study has a treatment in order to give an ethical dilemma effect on participants in decision making. The sample of this study was 48 active students of Soegijapranata Catholic University Semarang who have taken Cost Accounting courses. This study uses DIT (Define issue test) on cognitive moral development and SPSS programs. The results showed that individuals with high levels of cognitive moral development tend to be more honest in reporting budgets so that it can be said that cognitive moral development affects the honesty of budget reporting. Under optimal hurdle contract, individuals tend to be more honest in reporting budgets than in contract trust conditions so it can be said that there are differences in cognitive moral development in honesty of budget reporting. Key words: cognitive moral development, honesty of budget reporting Abstrak Penelitian ini bertujuan untuk menganalisis dampak Cognitive Moral Development dalam kejujuran pelaporan anggaran karena kejujuran pada karyawan merupakan hal yang penting dalam keberhasilan suatu perusahaan sehingga perlu dibentuk sejak dini. Cognitive Moral Development merupakan dasar pembenaran dalam pengambilan keputusan yang berkaitan dengan tindakan sosial untuk bertindak etis. Kejujuran pelaporan anggaran dalam penelitian ini memiliki treatment untuk memberikan efek dilema etis pada partisipan dalam pengambilan keputusan. Sampel penelitian ini adalah 48 mahasiswa aktif Universitas Katolik Soegijapranata Semarang yang telah mengambil mata kuliah Akuntansi Biaya. Penelitian ini menggunakan DIT (Define issue test) untuk cognitive moral development dan program SPSS. Hasil penelitian menunjukan bahwa individu dengan tingkat cognitive moral development yang tinggi cenderung lebih jujur dalam melaporakan anggaran sehingga dapat dikatakan bahwa cognitive moral development berpengaruh terhdap kejujuran pelaporan anggaran. Pada kondisi optimal hurdle contract individu cenderung lebih jujur melaporkan anggaran dibandingkan pada kondisi trust contract sehingga dapat dikatakan bahwa terdapat perbedaan dalam cognitive moral development terhadap kejujuran pelaporan anggaran. Kata kunci: cognitive moral development, hurdle contract, trust contract kejujuran pelaporan anggaran